2007
DOI: 10.1002/bem.20381
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of low‐intensity extremely high‐frequency electromagnetic radiation: Frequency and power dependence

Abstract: Using a model of acute zymosan-induced footpad edema in NMRI mice, the frequency and power dependence of anti-inflammatory effect of low-intensity extremely high-frequency electromagnetic radiation (EHF EMR) was found. Single whole-body exposure of animals to EHF EMR at the intensity of 0.1 mW/cm(2) for 20 min at 1 h after zymosan injection reduced both the footpad edema and local hyperthermia on average by 20% at the frequencies of 42.2, 51.8, and 65 GHz. Some other frequencies from the frequency range of 37.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…At fixed intensity of 0.1 mW/cm 2 and exposure duration of 20 min, the antiinflammatory effect expressed frequency dependence. The most effective of the examined frequencies were 37.5, 42.2, 51.8, and 65 GHz; while some other ''therapeutic'' frequencies, for example, 53.57 and 61.22 GHz, accepted for so-called EHF-therapy, were less effective or not effective at all with respect to the studied inflammatory process [Gapeyev et al, 2008]. Detailed study of the effect dependence on frequency in a narrow range from 42.0 to 43.0 GHz (with a step of 200 MHz) has shown quasi-resonance character of the effect with the Q-factor of about 70.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…At fixed intensity of 0.1 mW/cm 2 and exposure duration of 20 min, the antiinflammatory effect expressed frequency dependence. The most effective of the examined frequencies were 37.5, 42.2, 51.8, and 65 GHz; while some other ''therapeutic'' frequencies, for example, 53.57 and 61.22 GHz, accepted for so-called EHF-therapy, were less effective or not effective at all with respect to the studied inflammatory process [Gapeyev et al, 2008]. Detailed study of the effect dependence on frequency in a narrow range from 42.0 to 43.0 GHz (with a step of 200 MHz) has shown quasi-resonance character of the effect with the Q-factor of about 70.…”
Section: Introductionmentioning
confidence: 87%
“…To test the ability of low-intensity EHF EMR to induce anti-inflammatory effects, we used a technique of zymosan-induced paw edema previously described in Gapeyev et al [2006Gapeyev et al [ , 2008. Briefly, 25 ml of zymosan suspension (5 mg/ml) was subcutaneously injected into the plantar surface of the left hind paw of mice under light ether anesthesia.…”
Section: Model Of Acute Inflammationmentioning
confidence: 99%
“…The specific absorption rate on the surface of skin of the animals back was calculated by the formula [20] …”
Section: Methodsmentioning
confidence: 99%
“…We have shown that the exposure of animals with local and systemic inflammation to EHF EMR with certain physical parameters induced pronounced anti-inflammatory effects [6,7]. The anti-inflammatory effects of EHF EMR were accompanied with significant decrease in DNA damage of peripheral blood leukocytes and neutrophils [8].…”
Section: Introductionmentioning
confidence: 96%